2015
DOI: 10.1007/s10812-015-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of New Spectrophotometric Methods to Determine Enrofloxacin in Pharmaceuticals

Abstract: UDC 535.243:615.45 Four spectrophotometric methods, based on oxidation with cerium(IV), are investigated and developed to determine EFX in pure form and in dosage forms. The fi rst and second methods (Method A and method B) are direct, in which after the oxidation of EFX with cerium(IV) in acid medium, the absorbance of reduced and unreacted oxidant is measured at 275 and 320 nm, respectively. In the third (C) and fourth (D) methods after the reaction between EFX and oxidant is ensured to be completed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The literature review revealed that, several analytical methods have been reported for determination of ENR in pure form and pharmaceutical preparation using spectrophotometry [20][21][22][23][24][25][26][27], spectrofluorimetry [27][28][29][30][31][32], electrochemical [33][34][35], Capillary electrophoresis [36], and HPLC [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review revealed that, several analytical methods have been reported for determination of ENR in pure form and pharmaceutical preparation using spectrophotometry [20][21][22][23][24][25][26][27], spectrofluorimetry [27][28][29][30][31][32], electrochemical [33][34][35], Capillary electrophoresis [36], and HPLC [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%